Reciprocating wear behaviour of Ti alloy for biomedical materials - Chua, Kia Heen. (2013)
Many improvements of biomedical materials have been done to improve the lives of the elderly as well as the injured. Understanding biomaterials is of great importance as it will help in reducing wastage of materials and also reduce the cost of manufacturing.